Pendekatan Kultural sebagai Strategi Resolusi Konflik: Kasus Khon Kaen Thailand - Maika, Amelia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2006)
People would not only believe culture as a way of life, but also practicing them for several reasons including for a problem solving method. The assumptions rest on the values that determine peoples behavior in their social interaction. Cultural approach is one strategy in resolving conflict. Unfortunately, limited knowledge has led them to adapt their culture not in the right way. The mal-adoption in practicing culture becomes an obstacle for resolving conflict.The problems to be discussed centre on how to transform the obstacle to the conflict management strategy. It is important to socialize the urgency of resolving conflict, recommending the strategies to create a space for people to communicate and discuss their problems. Establishing a forum for discussion will encourage people participation.